2022
DOI: 10.3390/healthcare10040641
|View full text |Cite
|
Sign up to set email alerts
|

Profit or Purpose: What Increases Medical Doctors’ Job Satisfaction?

Abstract: This study integrates two competing views to examine whether medical doctors are satisfied with their jobs when they perceive their hospitals as being oriented toward profit (i.e., rational choice theory) or purpose (i.e., public service motivation). Using a sample of 127 doctors from 70 hospitals, this study tests these competing views. The results show that doctors who perceive their hospitals as purpose-driven are likely to experience job satisfaction, and this pattern still holds even if they also perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Winit and Kantabutra, 2017) and rational choice theory (e.g. Chang et al. , 2022) were seldomly applied in the literature on CSR and happiness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Winit and Kantabutra, 2017) and rational choice theory (e.g. Chang et al. , 2022) were seldomly applied in the literature on CSR and happiness.…”
Section: Resultsmentioning
confidence: 99%
“…Academic literature on this issue has mostly focused on one of the stakeholders and researched the effect of CSR practices on these groups. The most frequently studied issue is the effect of CSR on employees where topics such as employee psychology (Jeong et al, 2022b), job satisfaction (Chang et al, 2022), knowledge sharing of employees (Chtioui et al, 2022) and their life satisfaction (Lee et al, 2018) were researched. Customers form the other stakeholder group that is subject to numerous studies where the effect of CSR was questioned on subjects such as customer evaluations of the company with respect to meeting shareholder demands and being a socially responsible corporation (Gertner and Rifkin, 2018), brand equity judgements of customers (Kang and Namkung, 2018) and satisfaction, trust and loyalty of customers (Lombart and Louis, 2014).…”
Section: Corporate Social Responsibility (Csr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Yuan et al ( 2021 ) found that the satisfaction level of health workers is related to their monetary income. Chang et al ( 2021 ) examined that the service motivation theory is valid for doctors’ job satisfaction. Also, Ni et al ( 2022 ) declared that rewards and salaries are among the most important factors for job satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%